Is Nigeria Really “Big for Nothing”? Matters Arising from Kevin Nwabugwu Echeruo’s 1969 Propaganda Poster - Etiido Effiongwilliam Inyang; Basil S. Nnamdi (Celt: A Journal of Culture, English Language Teaching & Literature, 2019)
The audacious declaration “Big for nothing” in Kevin Echeruo’s propaganda poster during the Nigerian civil war offers illumination to the forgotten undercurrents that drove the 30-month war which in the last fifty years has contributed to the setting of agenda for separatist polemics in the Nigeria nation-state. Using largely the iconographic approach to visual description and interpretation, this study examines the cultural codes and representational conventions that inform contemporary artistic representational style as a cultural practice. The illustration not only approximates to one of the early visual indicators on the divisive national challenge rendered in highly coded visual and linguistic rhetoric of hegemonic power struggle by the elite class, but also a significant metaphor of contemporary frustration on nationhood and nationality for most Nigerians. Accordingly, this article broaches on the parameters of patriotism, nationality and self-determination to posit that the illustration represents the extremes of citizen dissatisfaction couched in a radical artistic narrative of a caricature. It submits that the strength of national allegiance and cohesiveness is a function of the reciprocity to its citizens.